Melatonin Delays Brain Aging by Decreasing the Nitric Oxide Level - Akbulut, K.G.; Guney, S.; Akgun, H.N.; Aktas, S.H.; Akbulut, H.; Cetin, F. (Нейрофизиология, 2013)
Aging is believed to be a first-order risk factor for most neurodegenerative disorders. The neuronal cell loss that occurs with aging has been partly attributed to increased production of nitric oxide and high caspase activity. Melatonin (MLT) might have a role in the regulation of nitric oxide in the brain. We investigated the effects of MLT on the nitrite/nitrate levels and caspase-3 enzyme activity in the frontal cortex, temporal cortex, and hippocampus of young and aged rats. There was no significant difference between the nitrite levels in the frontal cortex and hippocampus of young and aged animals. In the temporal cortex of aged rats, the nitrite level, however, was significantly higher (P < 0.001). In the aged group, MLT significantly decreased these levels in the brain regions. Caspase-3 enzyme activity in the temporal and frontal cortices was significantly higher in aged rats when compared to the control group (P < 0.05). Melatonin did not cause significant changes in caspase-3 activity in any brain region of both young and aged rats. Thus, brain regions demonstrate different caspase-3 enzyme activities and nitrite levels in the aging process. Exogenous MLT administration might delay brain aging (by moderation of death of neurons and glia) via decreasing the nitrite level.